Green sample preparation protocol for extraction of carbazoles from petroleum source rock - Akinsehinwa Akinlua; Kai Mangelsdorf (Heliyon)
A new green method for extraction of carbazoles from petroleum source rocks was developed using surfactant solution. A three-level full factorial design of experiment (DoE) which involved extraction temperature, extraction time and concentration of surfactant solution led to the development of a new extraction method avoiding organic solvents. All carbazoles extraction experiments were carried out with the assistance of a microwave oven. The carbazoles in the surfactant extracts were determined by high performance liquid chromatography-mass spectrometry (HPLC-MS). The results showed that temperature, time and concentration of surfactant solution have significant influence on the extraction yields of the carbazoles. The highest extraction yields for most of the carbazoles were obtained at the optimal conditions of extraction temperature of 110 °C, extraction time of 25 min and surfactant concentration of 0.02 M. In comparison with a fast organic solvent-based extraction method (accelerated solvent extraction, ASE) the microwave assisted surfactant extraction (MASE) method was more efficient with a very good reproducibility.